Robert Louis Stevenson and romantic tradition - Eigner, Edwin M. (Princeton legacy library., 1966)
Stevenson's fiction is evaluated in the light of the significant Romantic traditions that have influenced the novel and the romance. Stevenson is also considered as a serious writer and compared with Joseph Conrad, Mark Twain, and other major writers of the period. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.